Fatigue crack propagation behavior of high-strength steel under variable amplitude loading. (15th April 2021) - Tu, Wenjie; Yue, Jingxia; Xie, Hao; Tang, Weiguo
Highlights: Fatigue crack growth rate (FCGR) for high-strength steel was studied experimentally. FCGR under various overload ratio, overload interval, and load sequence was obtained. FCGR under 'Storm model' and superimposed loadings was obtained. Plastic zone around crack tip was obtained by digital image correlation (DIC) method. FCGR was predicted by a modified Wheeler model combined with DIC method. Abstract: In this paper, aimed at high strength steel for marine structures, a series of crack propagation tests were designed and carried out, and the influence of different load forms on crack growth has been investigated. At first, a series of fatigue crack propagation experiments were designed for compact tension specimens made of AH36 High-strength steel, and the influences of overload ratio, interval of overloads, and load sequence on fatigue crack growth rate were investigated. Besides, storm model loading and superimposed loading were applied to further investigate crack growth behavior under more complex loading condition. The research indicates fatigue crack growth behavior under variable amplitude loadings deviates apparently. The difference is mainly caused by the sequence of variable amplitude loadings and the retardation/acceleration when tensile/compressive overloads are applied. Moreover, digital image correlation technique was adopted to obtain the strain fields and residual strain around crack tip. The mechanism of fatigue crack growth behavior under variable amplitude loadings was investigated by analyzing the transformation of strain fields in crack tips. Extended finite element method to calculate the plastic zone size around crack tip was proposed and verified to be accurate and applicable. In the end, the plastic zone size obtained by digital image correlation technique, which shows better accuracy, was applied to improve the modified Wheeler model, and the fatigue crack growth behavior under variable amplitude loadings was predicted by the improved modified Wheeler model, and was in good agreement with experiment results.